Renal effects of a novel endogenous natriuretic agent xanthurenic acid 8‐o‐β‐d‐glucoside in rats. Issue 6 (13th November 2013) - Hoffman, Aaron; Okun‐Gurevich, Marina; Ovcharenko, Elena; Goltsman, Ilia; Karram, Tony; Cain, Cristopher; Abassi, Zaid; Winaver, Joseph
Abstract: Xanthurenic acid 8‐ o‐β ‐d ‐glucoside is an endogenous derivative of tryptophan metabolism, isolated from urine of patients with chronic renal disease. This compound was suggested previously to act as a natriuretic hormone based on its ability to block short circuit currents in a frog skin assay and to induce a sustained natriuresis when injected into rats (C. D. Cain et al., Proc. Natl. Acad. Sci. USA 2007: 17873–17878). The present communication describes the effects of the compound on renal clearance and hemodynamic parameters in male Sprague–Dawley rats maintained on a normal salt (0.4–0.5%) diet. Intravenous administration of synthetic xanthurenic acid 8‐ o‐β ‐d ‐glucoside in two consecutive incremental doses (6.3 and 31.5 nmol) resulted in a significant increase ( P < 0.05), in urine flow (43.91 ± 6.31 μ L/min vs. 10.54 ± 2.21 μ L/min), absolute rate of sodium excretion (3.99 ± 0.95 μ Eq/min vs. 1.15 ± μ Eq/min), and percentage sodium excretion (1.63 ± 0.46% vs. 0.37 ± 0.12%, peak response vs. baseline, respectively). The natriuretic/diuretic effect was associated also with a significant increase in potassium excretion. These effects were not related to changes in renal hemodynamics or in arterial blood pressure. Pretreatment with the sodium channel blocker, amiloride, completely abolished the natriuretic and kaluretic actions of the compound. Administration of the xanthurenic acid derivative caused a dose‐related increase in urinary nitrite/nitrate excretion. Moreover, under chronic nitric oxide blockade byl ‐NG‐Nitro‐Arginine‐Methyl‐Esther (l ‐NAME) sodium excretion was similar in rats treated or untreated with the compound. Our data demonstrate that xanthurenic acid 8‐ o‐β ‐d ‐glucoside has significant diuretic/natriuretic and kaluretic properties. An intact amiloride‐sensitive sodium channel is required for the renal effects of the compound. The data further suggest that the natriuretic effect is mediated in part by a nitric oxide‐dependent mechanism. Abstract : e00155 Xanthurenic glucoside is a new endogenous mild natriuretic/diuretic agent acting on amiloride‐sensitive renal epithelial sodium channels. In addition, the in vivo natriuretic effects are partially mediated by NO‐dependent mechanisms.